2017
DOI: 10.4028/www.scientific.net/ssp.265.296
|View full text |Cite
|
Sign up to set email alerts
|

Use of Low-Grade Vegetable Raw Materials in Production of Composites by Preliminary Processing

Abstract: Intensive cutting down of trees to replenish the reserves of business wood exhausts wood stocks in traditional logging areas, leads to the decrease in the areas of forest plantings.\, and ecological disruption. Now there are real opportunities to reduce the consumption of traditional forest resources thanks to fuller use of forest products, low-grade wood, and waste of sawmilling and a woodworking for the production of composite materials. In this regard the results of the research on the possibility to use lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Traditional synthetic polymers and composites based on them, in particular, polyethylene, despite the successful combination of production technology, the possibility of varying physical and mechanical characteristics and prices, create significant problems for ecology and the environment. An analysis of the scientific literature indicates that the solution to this problem is seen in the use of biopolymers or their combination with environmentally friendly fillers [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional synthetic polymers and composites based on them, in particular, polyethylene, despite the successful combination of production technology, the possibility of varying physical and mechanical characteristics and prices, create significant problems for ecology and the environment. An analysis of the scientific literature indicates that the solution to this problem is seen in the use of biopolymers or their combination with environmentally friendly fillers [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of wood species have poor adhesion to some adhesives, which is also a significant disadvantage, since this characteristic is important in the production of large-span laminated wooden structures, where the quality of the adhesive layer plays an important role. As a result of all of the above, it can be concluded that increasing the physical and mechanical qualities of lowgrade wood and increasing its adhesive qualities should be considered among the main issues to be addressed in the construction industry [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, structures made of wood composites are gaining in more popularity in the construction industry [1][2][3][4]. Composites are widely used in construction due to the advantages of the cast-in-place composition obtained.…”
Section: Introductionmentioning
confidence: 99%